Modelagem da hidratação de grãos de ervilha segundo a hipótese de volume constante - Omoto, Edilson Sadayuki (2007)
Mathematical models for estimating water concentration in pea grains during their hydration were developed from a transient water mass balance, inside a grain of pea, considering a constant volume and spherical geometry. These models are represented by an ordinary first order differential equation and have the following parameters: the mass transfer coefficient (Ks) or mass transfer effective coefficient (K's) and the equilibrium concentration (PAeq). The parameters have been numerically fitted using as criterion, the minimization of the sum-of-squared residuals or for a simple one using the linear correlation. For the model validation experimental data was measured from hydration test where grain peas were immersed in Iiquid water at constant temperature (10, 20, 30, 40, 50 or 60c). Additionally these models had been compared between itself and with literature empirical models. There was not practically temperature's influence on the equilibrium concentration, while Ks e K's, with increase temperature, does not vary iike linear fit.